Changes in the spectrum of protein components and the concentration of phospholipids of the erythrocyte membrane in patients with ulcerative colitis - O. V. Sai; Yu. I. Pivovarov; L. A. Dmitrieva; A. S. Sergeeva (Acta Biomedica Scientifica, 2021)
Ulcerative colitis is a chronic inflammatory bowel disease with unclear etiology. An insufficient amount of data on the etiopathogenetic mechanisms of the disease creates opportunities to research them at the cellular level, including the membrane level. Since the functional state of the cytoplasmic membrane largely depends on protein-lipid interactions, we studied the effect of the proportional ratio of three proteins (glucose transporter, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and glutathione-S-transferase (GST)) on the level of phosphatidylethanolamine and phosphatidylcholine in the erythrocyte membrane of patients with ulcerative colitis during an acute attack. The study involved 51 patients with ulcerative colitis during the acute attack and 26 clinically healthy individuals. The groups are comparable by gender and age to study the proteins of the cytoplasmic membrane, Laemmli electrophoresis technique in polyacrylamide gel was used, followed by an assessment of the intensity of protein bands staining on electropherograms. Phospholipid fractions were obtained using thin-layer chromatography and their content was assessed using the Mathcad 2001 Professional system. Statistical processing was carried out by the program Statistica 10.0 for Windows. Changes of phosphatidylcholine and phosphatidylethanolcholine levels in patients and healthy individuals are not of the same type and are interrelated with changes in the proportion of membrane proteins of the glucose transporter, GAPDH and GST. The proportions of proteins that affect the level of phospholipids have calculated. In patients with ulcerative colitis, a decrease in the level of the studied membrane lipids have revealed in comparison with the clinically healthy group, in addition, an increase in the proportion of the glucose transporter and a decrease in the proportion of GST have noted. In addition, the relationship between an increase in the level of the cytoplasmic membrane phospholipids in ulcerative colitis and a change in the proportion of GAFDH in a smaller direction, which slows down the process of glucose oxidation, was determined. The obtained data confirm the strengthening of the processes of antioxidant protection and the increased need for energy supply of the cell membrane in patients with ulcerative colitis during an acute attack.